2020
DOI: 10.1101/2020.08.14.20175125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence of Non-Adherence in Patients with Resistant Hypertension: a Systematic Review and Meta-Analysis

Abstract: Background: Resistant hypertension is quite prevalent and a risk factor for cardiovascular events. Patients with suspected resistant hypertension undergo more screening intensity for secondary hypertension, despite some of them being non-adherent to prescribed pharmacotherapy. The prevalence of non-adherence in this setting varies from about 5 to 80% in the published literature. Apart from the wide range, the relation between method of assessment and prevalence is not well established. Our objective was to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…This varied between 25% (95% CI 15 to 39%) using indirect methods of assessment and 44% (95% CI 32 to 57%) using direct methods of assessment. In this study, there was an association between higher prevalence of non-adherence with younger age, gender (higher prevalence of non-adherence in men compared with women), and higher rates of non-adherence were also seen in the more recent studies [ 13 ]. Efforts to diagnose and address non-adherence should be made in all patients with suspected RH.…”
Section: Adherencesupporting
confidence: 71%
See 1 more Smart Citation
“…This varied between 25% (95% CI 15 to 39%) using indirect methods of assessment and 44% (95% CI 32 to 57%) using direct methods of assessment. In this study, there was an association between higher prevalence of non-adherence with younger age, gender (higher prevalence of non-adherence in men compared with women), and higher rates of non-adherence were also seen in the more recent studies [ 13 ]. Efforts to diagnose and address non-adherence should be made in all patients with suspected RH.…”
Section: Adherencesupporting
confidence: 71%
“…Measures to improve medication adherence and the elimination of drugs and substances known to increase BP should be undertaken where possible. Management of medication non-adherence may include interventions such as reminders and pill packs as well as exploration into the reasons underlying non-adherence, which may include specific patient motives and beliefs pertaining to hypertension and its management [ 13 ].…”
Section: Management Of Resistant Hypertensionmentioning
confidence: 99%
“…Large observational studies have shown that roughly half of participants stop taking their antihypertensive drugs within a year for various reasons, including poor patient adherence, adverse effects of drug therapy, and socioeconomic factors. 9 A systematic review (SR) 11 published in 2020 reported that the prevalence of medication nonadherence was 35% in patients with resistant hypertension. Therefore, additional or alternative therapy is required for patients who cannot take medication or do not adhere to their prescribed regimen.…”
Section: What Is Renal Denervation?mentioning
confidence: 99%